Consumer Sovereignty in Healthcare: Fact or Fiction? - Sirgy, M. Joseph 1952-; Lee, Dong Jin; Yu, Grace B. (2011)
We pose the question: Is consumer sovereignty in the healthcare market fact or fiction? Consumer sovereignty in healthcare implies that society benefits at large when healthcare organizations compete to develop high quality healthcare products while reducing the cost of doing business (reflected in low prices), and when consumers choose wisely among healthcare products by purchasing those high quality products at low prices. We develop a theoretical model that encourages systematic empirical research to investigate whether consumer sovereignty in healthcare is fact or fiction. In doing so, we develop a series of theoretical propositions that may demonstrate that consumer sovereignty is more fiction than fact. Specifically, healthcare consumers lack the ability, motivation, and opportunity to choose healthcare products that are high in quality and low in price. Similarly, healthcare firms lack the ability, motivation, and opportunity to compete in ways to develop and market higher quality products at lower prices.
Keywords: healthcare economics; healthcare policy; healthcare reform; healthcare ethics; Consumer Sovereignty